Cryotherapy Has No Significant Effect on MMP-9 and TGF-β1 Expression in Fungal Corneal Ulcer - Dwita Permatasari; Hendrian Dwikoloso Soebagjo; Ismi Zuhria; Nila Kurniasari; Hari Basuki Notobroto; Cinintha Nandini (The Prodia Education and Research Institute (PERI), 2021)
BACKGROUND: Usually, surgical intervention is needed to eradicate the fungal microorganism that cause fungal corneal ulcers. However, since surgical intervention is invasive, the latest technology uses cryotherapy in treating it. Cryotherapy plays a vital role in the wound healing process. We aimed to evaluate is to study the decreased expression of matrix metalloproteinase 9 (MMP-9) and transforming growth factor β1 (TGF-β1) in fungal corneal ulcers after the administration of cryotherapy.METHODS: Aspergillus flavus fungus was injected to the intrastromal corneas of all Sprague Dawley rats. The rats were divided into four groups, the first group was not given any therapy, the second group was given topical natamycin therapy, the third group was given cryotherapy, and the fourth group was given a combination between cryotherapy and topical natamycin therapy. Therapy was given after five days of follow up on the formation of a corneal ulcer. After four days of therapy, the eyes were enucleated to determine MMP-9 and TGF-β1 expression.RESULTS: The result in the third group showed lower MMP-9 expression (20.0±10.0% cells per field of view) compared to the second group (40.0±20.0% cells per field of view) and the fourth group (30.0±25.0% cells per field of view), but had the same MMP-9 expression value as the first group. There was no significant difference in MMP-9 expression between the four groups (p=0.356). The third group reduced more TGF-β1 expression (10.0±12.50% cells per field of view) compared to the fourth group (30±27.5% cells per field of view) and the first group (30±32.5% cells per field of view). There was also no significant difference in TGF-β1 between the four groups (p=0.315).CONCLUSION: There is no significant difference in the expression of TGF-β1 and MMP-9 after the cryotherapy treatment.KEYWORDS: corneal ulcer, cryotherapy, MMP-9, TGF-β1